2014
DOI: 10.1016/j.jss.2014.03.069
|View full text |Cite
|
Sign up to set email alerts
|

Schlafen 12 expression modulates prostate cancer cell differentiation

Abstract: Background Schlafen proteins have previously been linked to leukocyte and intestinal epithelial differentiation. We hypothesized that Schlafen 12 (SLFN12) overexpression in prostate epithelial cells would modulate expression of prostate-specific antigen (PSA) and dipeptidyl peptidase-4 (DPP4), markers of prostatic epithelial differentiation. Materials and Methods Differentiation of the prostate cancer cell line LNCaP and PC-3 was compared after infection with an adenoviral vector coding for SLFN12-GFP (Ad-SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
(61 reference statements)
1
27
0
Order By: Relevance
“…SLFN12 has previously been reported to alter the phenotype of other cells, including prostatic cancer cells [53] and activated T cells [54, 55], and to inhibit dendritic cell differentiation [11]. Slfn4, also intermediate length, regulates myelopoiesis [56].…”
Section: Discussionmentioning
confidence: 99%
“…SLFN12 has previously been reported to alter the phenotype of other cells, including prostatic cancer cells [53] and activated T cells [54, 55], and to inhibit dendritic cell differentiation [11]. Slfn4, also intermediate length, regulates myelopoiesis [56].…”
Section: Discussionmentioning
confidence: 99%
“…Human SLFN11 has been shown to inhibit viral protein synthesis in HIV-infected cells (32) and to sensitize malignant cells to DNA-damaging agents and other chemotherapeutic cells (15). Human SLFN5 has been implicated in the control of anchorage-independent growth of malignant melanoma cells (18), while human SLFN12 has been im- plicated in the control of differentiation of prostate epithelial cells (13).…”
Section: Discussionmentioning
confidence: 99%
“…There are several human and mouse genes that are members of the SLFN family (9,11). Prior evidence has implicated members of the Schlafen family in the regulation of tumorigenesis (13)(14)(15)(16)(17)(18). Notably, expression of various members of this family is upregulated following treatment with type I IFNs (17)(18)(19), cytokines known to promote induction of antineoplastic, antiviral, and immunoregulatory effects (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…In contrast, the level of slfn4 is high in primitive bone marrow cells, but low in macrophages (van Zuylen et al, 2011). (4) Slfn members inhibit migration and invasion of cancer cells and sensitize cancers to chemotherapy (Kovalenko and Basson, 2014;Tian et al, 2014). In addition, recent studies have shown that slfn protein can serve as markers of gastric metaplasia (Ding et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific location and relative functions of human slfns are not well understood. H-slfn5 was identified to localize in the nucleus (Katsoulidis et al, 2010), while h-slfn12 and h-slfn11 were indicated to localize in the cytosol (Li et al, 2012;Kovalenko and Basson, 2014).…”
Section: Introductionmentioning
confidence: 99%